Impact of educators' perceptions on the guidance and counselling programme: A case of Hwange urban secondary school - Bhiri, Kuziwa (Journal of Advanced Guidance and Counseling, 2025)
Purpose – This study examines the impact of educators’ perceptions on the effectiveness of the Guidance and Counselling (G&C) programme in Hwange Urban secondary schools. The objectives were to explore teachers’ attitudes toward G&C, determine how their perceptions influence programme implementation, and identify factors that facilitate or hinder successful delivery. Method – A qualitative research design was adopted, using semi-structured interviews and document analysis to collect in-depth data. The sample consisted of 20 participants, selected purposively: 12 teachers, 4 school counsellors, and 4 school administrators. Result – Findings revealed that while educators generally acknowledge the importance of G&C in promoting learners’ academic, social, and emotional well-being, inconsistent understanding of the programme, limited training, heavy workloads, and inadequate resources significantly impede effective implementation. Positive perceptions were associated with greater commitment, wider integration of G&C activities, and stronger support for learners. Implication – The study highlights the need for targeted professional development, institutional support, and policy reinforcement to enhance educators’ confidence and participation in G&C. Originality/Value – The originality of this article lies in its contextualised exploration of educators’ perceptions within a Zimbabwean urban setting, offering insights that can inform programme strengthening, policy formulation, and future research on school-based counselling services. *** Tujuan – Studi ini mengkaji dampak persepsi pendidik terhadap efektivitas program Bimbingan dan Konseling (B&K) di sekolah menengah perkotaan Hwange. Tujuan penelitian ini adalah untuk mengeksplorasi sikap guru terhadap B&K, menentukan bagaimana persepsi mereka memengaruhi implementasi program, serta mengidentifikasi faktor-faktor yang memfasilitasi atau menghambat pelaksanaan program yang sukses. Metode – Desain penelitian kualitatif digunakan, dengan wawancara semi-terstruktur dan analisis dokumen untuk mengumpulkan data mendalam. Sampel terdiri dari 20 peserta yang dipilih secara purposif: 12 guru, 4 konselor sekolah, dan 4 administrator sekolah. Hasil – Temuan menunjukkan bahwa meskipun pendidik umumnya mengakui pentingnya G&C dalam mempromosikan kesejahteraan akademik, sosial, dan emosional siswa, pemahaman yang tidak konsisten tentang program, pelatihan yang terbatas, beban kerja yang berat, dan sumber daya yang tidak memadai secara signifikan menghambat implementasi yang efektif. Persepsi positif terkait dengan komitmen yang lebih besar, integrasi yang lebih luas dari aktivitas G&C, dan dukungan yang lebih kuat bagi siswa. Implikasi – Studi ini menyoroti kebutuhan akan pengembangan profesional yang ditargetkan, dukungan institusional, dan penguatan kebijakan untuk meningkatkan kepercayaan diri dan partisipasi pendidik dalam G&C. Orisinalitas/Nilai – Keaslian artikel ini terletak pada eksplorasi kontekstual persepsi pendidik dalam lingkungan perkotaan Zimbabwe, yang menawarkan wawasan untuk memperkuat program, merumuskan kebijakan, dan penelitian masa depan tentang layanan konseling berbasis sekolah.